A fast response fluorescence probe specific for hypochlorous acid detection and its applications in bioimaging. Issue 12 (6th March 2018) - Jia, Hongmin; Xia, Shuhe; Feng, Huan; Meng, Qingtao; Duan, Chengchen; Zhang, Zhiqiang; Zhang, Run
Abstract : The features ofDNPH-NA, including its high sensitivity, selectivity, and reliability at physiological pH, together with a rapid response, enable its successful application in the detection of endogenous HOCl in vitro and in vivo . Abstract : Quantitative detection and visualization of hypochlorous acid (HOCl) in biological samples has emerged as a hot topic in biochemical research because of the important role of this biomolecule in live organisms. In this contribution, a novel 1, 8-naphthalimide-based fluorescence probe, DNPH-NA, was designed and synthesized for HOCl detection in aqueous solutions and in biological systems. In the presence of HOCl, significant changes in absorption and fluorescence spectra were observed, which allow for the quantitative detection of HOCl in PBS buffer. The detection limit for HOCl was determined to be 50 nM. In the presence of HOCl, the fluorescence response ofDNPH-NA was found to be completed within 2 seconds. The desirable features ofDNPH-NA for the detection of HOCl in aqueous solutions, such as its high sensitivity and selectivity, reliability at physiological pH, rapid fluorescence response, and biocompatibility enabled its application in the detection of HOCl in biological samples. Imaging of exogenous HOCl in live HeLa cells and endogenous HOCl generation in live J774A.1 macrophage cells and zebrafish was then successfully performed usingDNPH-NA as a fluorescence probe.